Oral Hygiene Awareness, Oral Health Condition and Number of Present Teeth in Elderly Outpatients in the Geriatric Dentistry of the Nippon Dental University - Suzuki, Akira; Watanabe, Akiko; Fukuda, Yoko; Inaba, Shigeru; Kikutani, Takeshi; Nakata, Kazumi; Nagashima, Kyoko; Nakagami, Maki; Ishida, Kanemitsu (Ronen Shika Igaku, 1994)
The relation between the oral hygiene awareness and the oral health condition of elderly patients is not well known. The purpose of this study was to investigate the relation between this awareness in elderly patients and their oral health condition. The subjects were a total of 115 (none edentulous) first visited patients of over 60 years, who visited the Department of Geriatric Dentistry of Nippon Dental University. An investigation of oral hygiene awareness and an observation of the oral condition were carried out. All the information about their awareness was obtained through interviews by dental hygienists. The relationships of the awareness to oral hygiene, plaque index and the number of present teeth were evaluated. The results were as follows ; 1.50 . 4% of subjects had received oral health instruction. More over 70 year old had received instruction than under 70 year olds . The number of present teeth was more in the subjects who had received the instruction than who had not . The oral health instruction, however, was not related to the awareness of the correct number of tooth brushings a day, the oral health condition and the loss of teeth . 2. PCR (Plaque Control Record) was 60.4% among the under 70 years olds and 81.1% among those of over 70 years olds. The oral health condition was very poor in both groups .The over 70s were poorer than the under 70s. 3. Many subjects with only a few present teeth said that there is no use complaining about the loss of teeth because of aging. The oral health condition was very poor in the subjects who have such attitude. 4. Most of the subjects brushed their teeth twice a day, The number of toothbrushings was not related to their oral health condition. From the above, toothbrushing was not recognized by the elderly as preventing dental disease and helping treatment. It appeared that elderly peopl's oral hygiene awareness was strongly influenced by their resignation due to aging and by their experience of loss .